Non- verbal communication and it’s role in supporting verbal communication in TV talk show programs - إباء أحمد التجاني عمر عوض (International Journal of Social Communication, 2023)
The study aims to identify the use of non-verbal communication and its role in supporting verbal communication during TV talk shows, using the content analysis of a sample of episodes of the of talk show programs on Sudan TV, during 19 December 2018 - 30 June 2019. The most important findings of the study, various forms of Non-verbal communication are used, focusing on hands movement and expression by using the volume, frequency and tone of the voice, the uniform dedicated for work and mixed colours overshadowed the clothes of the presenter and the participants of the episodes. Body and verbal languages overlap in most cases. The most prominent recommendations of the study are the importance of training broadcasters and program presenters to take advantage of body movement to the attract viewer, and the need to alert participants of TV programs for facing the camera more than facing the presenter because they address the viewers.